2003
DOI: 10.1055/s-2003-41518
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Nonanesthetist Sedation with Propofol for Outpatient Colonoscopy and Esophagogastroduodenoscopy

Abstract: Propofol can be safely administered for sedation during colonoscopy and esophagogastroduodenoscopy by nonanesthetists who are familiar with the pharmacological properties and use of this drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(20 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…Experiences with nurse-administered propofol sedation, abbreviated NAPS, have been reported from different centers in the US and Europe. Together, the authors have examined more than 20,000 NAPSs that took place at two different institutions: a tertiary university hospital and a hospital-based private practice [20, 23]. The overall reported safety of NAPS is well comparable to other methods.…”
Section: Advantages and Potential Risks Of The Drugmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiences with nurse-administered propofol sedation, abbreviated NAPS, have been reported from different centers in the US and Europe. Together, the authors have examined more than 20,000 NAPSs that took place at two different institutions: a tertiary university hospital and a hospital-based private practice [20, 23]. The overall reported safety of NAPS is well comparable to other methods.…”
Section: Advantages and Potential Risks Of The Drugmentioning
confidence: 99%
“…The overall reported safety of NAPS is well comparable to other methods. In more than 50,000 sedations, there has been no observed mortality, no need of endotracheal intubation and the incidence of brief mask ventilation was between 1:500 and 1:1,000 [9, 19, 20, 23, 31, 32, 47, 55, 59]. …”
Section: Advantages and Potential Risks Of The Drugmentioning
confidence: 99%
See 1 more Smart Citation
“…Propofol is a good candidate for the sedative agent in diagnostic EGD in that it is superior to benzodiazepines with regard to rapidity of induction of sedation and is associated with faster recovery. However, the possibility of respiratory depression has made many endoscopists reluctant to use propofol routinely [1,2,3,4,5,6,7,8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Although several large clinical trials have recently demonstrated the safety of new drugs (e.g. propofol) under careful patient selection and conventional surveillance, there is still an ongoing debate on the risk that patients may unintentionally slide into a level of deep sedation or even anesthesia where vital functions may be seriously impaired [1, 7, 8, 9, 10, 11, 12, 13]. Many doubts regarding the use of these drugs by non-anesthesiologists (e.g.…”
Section: Introductionmentioning
confidence: 99%